Adaptation of Learning Technology for Teachers of SD Negeri 2 Pakistaji During the Covid-19 Period - Fitrotin Azizah; Rani Wulandari; Triana Kartika Santi; Totok Hari Prasetiyo; Iis Ni’matul Jannah; Magdalena Putri Nugrahani; Ifa Muhimmatin (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2022)
The covid-19 pandemic has had a major impact on various sectors in Indonesia, one of them being the education sector. When online learning begins, teachers must adapt to various strategies and new media to ensure teaching and learning activities continue even when students are at home. But now after learning can be carried out in offline learning, educators need to re-adapt to this learning mode. The Teaching Campus Program is one solution to the problems faced by teachers during offline learning in the New Normal Era. This program aims to assist the adaptation of technology by teachers. This service is held at SD Negeri Pakistaji, Banyuwangi Regency. The activity was carried out for three months and was attended by teachers at SD Negeri Pakistani. The results of this activity examine the teacher's ability to operate digital devices as support.